Principles of Providing Nutrition to People Living with HIV/AIDS : A Literature Review - Ninuk Dian Kurniawati; Adi Sukma Septiana; Muhammad Iqbal; Laely Sholihah; Dyah Sekaringtyas Ciptaningrum; Yulita Thadea Retanubun (Critical Medical and Surgical Nursing Journal (CMSNJ), 2021)
Introduction: HIV patients with good nutritional status have a good immune system. Good nutritional status can inhibit the process of HIV disease entering the AIDS stage. In addition, good nutritional intake is needed so patients can maintain their health conditions during ARV treatment. This literature review aimed to explain the principles of nutritional fulfilment in HIV patients. Methods: The method used in this study is a literature review with predetermined inclusion and exclusion criteria. The number of articles obtained from the literature review results is 8 articles. The instrument used to evaluate the research is from The Joanna Briggs Institute (JBI). Results: A total of 8 articles met the inclusion and exclusion criteria. The results of the study assessment from the article achieved a score higher than 50% so that it met the Critical Appraisal criteria which would then be analyzed for data. Inadequate nutritional status in a person with HIV-AIDS (PLWHA) has a high risk of declining health in general. With good nutritional status, it can prevent HIV disease from entering the AIDS stage. Conclusion: Protein-energy enriched macronutrient supplementation and ARV initiation effectively improve physiological, nutritional status and immune response in PLWHA. This can prevent people living with HIV from experiencing malnutrition and wasting, restore the ideal body weight, increase and maintain the body's ability to fight various opportunistic infections, increase the effect of drugs, and improve and improve the quality of life of PLWHA patients.